DETERMINANTS OF MOBILE WALLET’S USAGE INTENSITY IN BANDUNG: HOW PERCEIVED TRUST MEDIATES THE USER PERCEPTION - Lutfie, Harrie; Widaningsih, Sri; Marcelino, Dandy (LPPM STIE Muhammadiah Bandung, 2022)
One of the organizations involved in the fintech DANA hailed the favorable trend of consumers using mobile wallets by utilizing digital services in novel ways, ranging from promotions to partnership with other industries. DANA, the digital wallet, has used a variety of marketing methods to build good user views. It is critical to consider the security of the digital wallet service, since the factor of trust in this study is thought to be a mediator that increases the link between DANA users' views and the intensity with which they use the DANA's mobile wallet. The goal of this study is to focus on user perceptions in order to increase user trust and intensity of usage of the DANA mobile wallet in the future. Explanatory statistics were used in this work, along with the SEM (Structural Equation Modeling) analytic approach, and the data was processed using the SMART PLS 3.2.9 data processing program. With a total of 400 responses, the researcher used incidental sampling as his sample strategy. According to the calculation results, the overall contribution of user perception has a direct impact on user trust. Then, based on the following set of calculations, the contribution of user perception and user trust is calculated, which has a direct impact on the intensity of usage.